The relationship between organizational communication and employees productivity with new dimensions of effective communication flow - Sadia, Aysha; Mohd Salleh, Berhannudin; Abdul Kadir, Zulida; Sanif, Sazuliana (CSRC Publishing, Center for Sustainability Research and Consultancy Pakistan, 2016)
Organisations can be run successfully, only if effective organisational communication takes place. A decision, whether strategic or operational, cannot be made without communication and the necessary information. There have been extensive researches on the relationship of organizational communication and productivity of employees’ in the past. However, this study examines the impact of Effective internal communication on productivity of employees’ in organization. The main focus of this research is the organizational communication level of employees behavior towards productivity which is deemed important to investigate their level of effective internal communication and employees’ productivity. This is a distinctive study, as the previous researches focused only on the relationship of organization communication and the productivity of organization, but this study focuses on the link between Organization communication and employees productivity with the help of effective communication. Once the effective communication is identified then the organizational communication and its relationship with the employees’ productivity is ascertained.